Study of Electrical Conductivity of Pyrrole-Reduced Graphene Oxide Pellet - Mohd Hizam, S.M. (Institute of Electrical and Electronics Engineers Inc., 2021)
Pyrrole-reduced graphene oxide was synthesized by chemical reduction because of its outstanding advantages including large surface area, high effective permittivity and electron mobility, and high electrical conductivity. This work reports on the detailed electrical conductivity study of pyrrole-reduced graphene oxide (py-rGO) coated on fluorine-doped tin oxide (FTO) glass. The py-rGO pellet is compressed by a pair of (3 cm x 2 cm) FTO glasses electrode was characterized by electrochemical impedance spectroscopy (EIS). Py-rGO was characterized by Fourier transform infrared (FTIR), Raman, X-ray powder diffraction (XRD) and X-ray photoelectron spectroscopy (XPS). The symmetric supercapacitor cell was made by putting rGO pellet in between of a pair of FTO glasses that has been soldered to act as anode and cathode. The electrical conductivity depends on the water hardness. Every types of water have different hardness. The conductivity of each rGO pellet before the water sample drop namely tap, distilled and lake water, are 1.154, 2.256 and 15.057 S/cm, respectively. Meanwhile, the conductivity of each rGO pellet after dropping are 5.168, 102.11 and 4.938 S/cm, respectively, showing that treated water has higher conductivity than untreated water. The changes in conductivity of the rGO pellet show that the conductivity of rGO pellet could be tuned by changing the condition of the water sample. Â© 2021 IEEE.